Adsorption of Cadmium on Cucumber Peel: Kinetics, Isotherm and Co-ion Effect. Issue 2 (3rd April 2018) - Basu, Mousumi; Guha, Arun K.; Ray, Lalitagauri
Abstract: The present study highlights the usage of cucumber peel as sorbent of cadmium. The biomass was the most appropriate one among other plant wastes tested. Sorption was governed by different physico-chemical parameters. The time period of 60 min was enough to complete the sorption process obeying the Lagergren pseudo-second-order kinetic model. Isotherm data fitted very well to the Langmuir model, and maximum adsorption capacity ( q max ) was 0.998 mmol g −1 . In a bimetallic system, the presence of lead significantly decreased the uptake of cadmium. Scanning electron microscopy–energy dispersive X-ray analysis and Fourier transform infrared spectroscopy were done to get a better understanding of the adsorption process. Carboxyl group was the primary metal-binding group as revealed from modification of functional group study. One-hundred millimolars of HCl efficiently eluted adsorbed cadmium and refreshed the sorbent for further use.